ETHNOGRAPHY STUDY : THE CULTURAL AND SOCIAL BELIEFS OF JUNIOR PROGRAMMERS - Raden Maart Adi Waskita Tjahjono; Jerry Heikal (PT. Media Akademik Publisher, 2024)
This ethnography study examines the cultural and social beliefs of junior programmers, with a particular focus on their beliefs and values related to speed in completing tasks. The study draws on data from interviews with a group of junior programmers, as well as observations of their work practices. The findings of the study suggest that junior programmers operate within a complex cultural and social environment that shapes their beliefs about speed. On the one hand, junior programmers are often under pressure to complete tasks quickly, both from themselves and from their peers and supervisors. This pressure can be driven by a number of factors, including the fast-paced nature of the software industry, the competitive job market, and the desire to prove themselves. On the other hand, junior programmers also value quality work and want to produce code that is well-written and bug-free. This can sometimes lead to a conflict between speed and quality, as junior programmers may feel pressured to sacrifice quality in order to meet deadlines. The study also finds that junior programmers' beliefs about speed are influenced by their social and cultural backgrounds. For example, junior programmers from cultures that value hard work and dedication may be more likely to prioritize speed over quality. Similarly, junior programmers who come from competitive environments may be more likely to feel pressure to work quickly. The study concludes by discussing the implications of these findings for both junior programmers and the software industry. For junior programmers, the study highlights the importance of developing strategies for balancing the pressure to complete tasks quickly with the need to produce high-quality work. For the software industry, the study suggests a need to create a culture that values both speed and quality, and that supports junior programmers in developing healthy and sustainable work habits.